Aggregation deaggregation influenced selective and sensitive detection of Cu2+ and ATP by histidine functionalized water-soluble fluorescent perylene diimide under physiological conditions and in living cells1. Issue 36 (23rd April 2015) - Muthuraj, Balakrishnan; Chowdhury, Sayan Roy; Mukherjee, Sudip; Patra, Chitta Ranjan; Iyer, Parameswar Krishnan
<x xml:space="preserve">Abstract</x> A novel PDI-HIS probe detects Cu2+ to form aggregated nonfluorescent complex. Addition of 0.58 ppm ATP to this complex causes its rapid disaggregation thereby recovering the fluorescence by ∼99% in vitro and in A549 living cells.